FAPS system: A prototype for lean manufacturing scheduling in footwear - Reyes, John (2017)
The research develops an industrial software application called FAPS System for the planning and scheduling manufacturing. It contains three modules used for planning and programming of resources, process management and Andon module focused on the use of lean manufacturing techniques for the notification, emission and display of contingencies presented during the production in real time. A case study is described in Ecuadorian footwear companies for the execution of experimental prototype efficiency tests. Through the unified modeling language diagrams, the requirements and functionalities of the software developed based on private and free technologies are defined. The planning module has a scheduling algorithm of days based on weighted standards that allows to estimate the delivery date of a production order, reprogram it and compare the planned quantity with respect to the capacity used. The Andon module is an Android application that consumes the information managed in the planning and process modules, thereby monitoring in real time the state of the plant and the production progress. The experimental results show that the system is adaptable to multiproduct orders and the scheduling allows to increase 6% the utilization percentage of the production processes.